AZO-modified zirconium dioxide antistatic pigment and low solar absorptivity antistatic thermal control coating and preparation method thereof
Zirconium dioxide is modified and combined with resin to prepare a double-layer structure with low solar absorption rate anti-static thermal control coating, which solves the problems of high solar absorption rate and poor radiation resistance of existing coatings, and achieves efficient thermal control and radiation resistance.
Patent Information
- Application Number
- CN202410684797.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-05-30
AI Technical Summary
The existing coating anti-static thermal control coating has a large solar absorption rate, which makes it difficult to effectively control the temperature in spacecraft applications and is intolerant to electronic radiation.
Zirconium dioxide is modified through atomic layer deposition technology, which gives it anti-static function and is combined with resin to prepare a double-layer structure with low solar absorption anti-static thermal control coating through spraying and other processes.
The anti-static thermal control coating with low solar absorption, high emissivity and high stability has been achieved, which significantly improves the coating's resistance to electron radiation and meets the spacecraft's demand for anti-static thermal control coatings.
Smart Images

Figure CN118668178B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal control material preparation, and specifically relates to a method for preparing an AZO-modified zirconium dioxide antistatic pigment, and a low solar absorption antistatic thermal control coating and a method for preparing the same. Background Art
[0002] Thermal control coating is an important part of the thermal control system of spacecraft. It uses the thermal radiation characteristics of the coating surface to change the surface thermophysical properties of the spacecraft, so as to effectively control the temperature of the spacecraft in the radiation heat exchange, so that the temperature of the internal instruments and equipment does not exceed or is lower than the allowable range during the internal and external heat exchange process, so as to ensure the normal working environment inside the artificial celestial body. Its principle is to adjust the solar absorption rate αs and infrared emissivity εh of the surface of the object to control the thermal balance of the object.
[0003] The geomagnetic substorm environment in the geosynchronous orbit (GEO) environment has a serious charging and discharging effect. The settling electrons in the polar orbit will cause the charge to accumulate on the thermal control coating on the satellite surface. When the breakdown threshold is exceeded, the satellite surface will discharge, which will cause great damage to the satellite. Since most of the outer surface of the satellite is covered with thermal control coating, the purpose of anti-static can be achieved by improving the conductive properties of the thermal control coating, such as coating a layer of indium tin oxide transparent conductive film on the outer surface of the secondary surface mirror reflective thermal control coating, adding anti-static pigments to the coating type thermal control coating, etc. However, the solar absorption rate of coating type anti-static thermal control coatings at home and abroad is relatively large, so it is urgent to improve the optical properties of coating type anti-static thermal control coatings. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an AZO-modified zirconium dioxide antistatic pigment and a low solar absorptivity antistatic thermal control and a preparation method thereof in view of the problems existing in the prior art. Figure 1 The thermal control coating of the present invention is mainly used for the outer surface of spacecraft such as space satellites, and has excellent characteristics such as low solar absorption rate, high emissivity, high stability, and easy preparation.
[0005] The present invention utilizes atomic layer deposition technology to modify zirconium dioxide, giving it an antistatic function, and prepares a low solar absorption antistatic thermal control coating by spraying and other processes. The preparation method is simple and easy, easy to prepare on a large scale, and the quality of the obtained antistatic coating product is controllable.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing an AZO-modified zirconium dioxide antistatic pigment, wherein zirconium dioxide powder is placed in an ALD reaction chamber and then processed according to the following steps:
[0008] Step 1: react with a zinc source in a nitrogen environment, and clean the reaction environment after the reaction is completed;
[0009] Step 2: reacting with an oxygen source under the same conditions as step 1, and cleaning the reaction environment after the reaction is completed;
[0010] Step 3: Repeat steps 1 and 2 in sequence;
[0011] Step 4: react with an aluminum source under the same conditions as step 1, and clean the reaction environment after the reaction is completed;
[0012] Step 5: Repeat step 2;
[0013] Step 6. Repeat steps 1 and 5 at least once; you are done.
[0014] It is further defined that completing the operation of steps one and two once is a sub-cycle, and completing the operation of steps one to five once is a main cycle; the number of sub-cycles is set according to the zinc-aluminum ratio; and different main cycles are determined according to anti-static requirements.
[0015] It is further defined that the ratio of zinc to aluminum is (8-50):1; and the particle size of the zirconium dioxide powder is 50nm-1μm.
[0016] It is further defined that the deposition parameters are as follows: the zinc source is diethyl zinc or dimethyl zinc, the oxygen source is ultrapure water, and the aluminum source is trimethyl aluminum; the deposition temperature is 100°C-150°C; the chamber pressure is 20Pa-100 Pa, the zinc source pulse time is 10s-60s, the oxygen source pulse time is 10s-60s, and the aluminum source pulse time is 10s-60s; the reaction environment is cleaned by the following operation: each zinc / aluminum source pulse is followed by a 20s-60s high-purity nitrogen purge, the oxygen source pulse is 10s-60s, and then a 20s-60s high-purity nitrogen purge is used to flush away reaction by-products and residual reaction sources.
[0017] The coating of the present invention adopts a double-layer coating structure, the bottom layer is a zirconium dioxide-based high-reflection layer, and the surface layer is an ALD-modified zirconium dioxide-based antistatic coating. The double-layer coating structure enables the composite coating to have an extremely low solar absorption rate and an antistatic function, thereby improving the coating's resistance to electron radiation.
[0018] The present invention also provides a method for preparing a low solar absorptivity antistatic thermal control coating, comprising the following steps:
[0019] Step 1, weigh the binder and the solvent, add the additive and zirconium dioxide powder after the binder is completely dissolved, disperse at a speed of 1000rpm-2000rpm for 1h-3h, filter and apply on the pre-treated substrate, cure at 25℃-125℃ for 2h-24h, and obtain a high reflective layer on the surface of the substrate;
[0020] Step 2, weigh the binder and the solvent, and after the binder is completely dissolved, add the additive and the AZO modified zirconium dioxide antistatic pigment prepared by any of the above methods, disperse at a speed of 1000rpm-2000rpm for 1h-3h, filter and apply on the high reflective layer prepared in step 1, and cure at 25℃-125℃ for 2h-24h to obtain an antistatic coating on the surface of the high reflective layer; that is, it is completed.
[0021] It is further defined that in step 1, the mass ratio of the binder to the zirconium dioxide powder is (2-6):1, and the thickness of the high reflective layer is 100 μm-150 μm.
[0022] It is further defined that in step 1, the particle size of the zirconium dioxide powder is 50nm-1μm;
[0023] It is further defined that in step 2, the thickness of the antistatic coating is 30 μm-50 μm;
[0024] It is further defined that in steps 1 and 2, the binder is a binder for the coating; it can be an inorganic resin such as silica sol, potassium silicate, lithium silicate, or a low condensable volatile resin such as acrylate, isocyanate, silicone resin, epoxy resin, etc.;
[0025] It is further defined that in steps 1 and 2, the solvent is anhydrous ethanol, acetone or water;
[0026] It is further defined that in steps 1 and 2, the auxiliary agent is an organosiloxane.
[0027] The present invention also provides an antistatic thermal control coating with low solar absorption rate prepared by any of the above methods.
[0028] The thermal control coating of the present invention has a white appearance, a coating thickness of 100-200 μm, a solar absorptivity of 0.06-0.15, a hemispherical emissivity of 0.88-0.92, a radiation absorption ratio of 0.11-0.15, a total mass loss TML <1%, a condensable volatile matter CVCM <0.1%, and a volume resistivity of ≤1.0×10 7 Ω·m, after 300 thermal cycle tests at -196℃~125℃, the coating has no cracking, peeling, blistering and other phenomena, stable optical properties and good adhesion, which basically meets the needs of spacecraft for antistatic thermal control coatings and improves the space environment stability of paint-type thermal control coatings for spacecraft.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The double-layer structure low solar absorptivity antistatic thermal control coating prepared by the present invention has excellent initial thermal control performance, and the radiation absorption ratio is less than 0.15, achieving the leading level in the industry;
[0031] The double-layer antistatic thermal control coating prepared by the present invention has a simple preparation process and can be prepared on a large scale. The prepared zirconium dioxide-based antistatic thermal control coating has greatly improved electron radiation resistance, which can ensure the reliability of spacecraft operation and meet the spacecraft's requirements for the stability of the coating-type thermal control coating in the space environment.
[0032] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Schematic diagram of a double-layer structured low solar absorptivity zirconium dioxide-based antistatic thermal control coating;
[0034] Figure 2 The cross-cut test results of the comparative example and the embodiment;
[0035] Figure 3 Optical images of the coatings of Example 1 and Comparative Example 1 after electron irradiation;
[0036] Figure 4 This is the solar reflection spectrum of the coating in Example 1 before and after electron irradiation. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.
[0038] The present invention provides a method for preparing a low solar absorptivity antistatic thermal control coating, which specifically comprises the following steps:
[0039] Step 1: Preparation of AZO-modified zirconium dioxide antistatic pigment: zirconium dioxide powder (granules) is subjected to ALD modification treatment, and an antistatic AZO layer is deposited on the surface of the zirconium dioxide powder to form a new antistatic thermal control pigment;
[0040] Step 2. Preparation of zirconium dioxide-based high reflective layer: weigh the binder and solvent, and after the resin is completely dissolved, add the additive and zirconium dioxide powder, disperse at 1000-2000rpm for 1-3h, filter and apply it on the pre-treated substrate, and cure at 25-125℃ for 2-24h to prepare the high reflective layer.
[0041] Step 3. Preparation of zirconium dioxide-based antistatic surface layer: weigh the binder and solvent, and after the resin is completely dissolved, add the additive and AZO-modified zirconium dioxide powder. Disperse at 1000-2000 rpm for 1-3 hours, filter and apply it on the zirconium dioxide-based reflective layer prepared in step 2. After curing at 25-125°C for 2-24 hours, a high reflective layer can be prepared.
[0042] Example 1
[0043] A low solar absorption antistatic thermal control coating of this embodiment is composed of a zirconium dioxide-acrylate high reflective layer and an AZO-modified zirconium dioxide-acrylate surface layer, and specifically involves the following process:
[0044] Preparation of ALD-modified zirconium dioxide-based antistatic thermal control pigments: Using ALD technology, AZO was modified on the surface of zirconium dioxide. The deposition parameters of ALD deposition of AZO are as follows: the zinc source is diethyl zinc, the oxygen source is water, and the aluminum source is trimethyl aluminum; the carrier gas is high-purity nitrogen; the deposition temperature is 125°C; the pressure in the cabin is 30Pa, the zinc source pulse time is 60s, the oxygen source pulse time is 60s, and the aluminum source pulse time is 60s; pulse and cleaning time: each zinc source and aluminum source pulse is followed by a 60s high-purity nitrogen cleaning; the oxygen source pulse is 60s, followed by a 30s high-purity nitrogen cleaning to wash away the reaction by-products and residual reaction sources, the zinc-aluminum ratio is 24:1, and the number of parent cycles is 2; the specific steps are as follows:
[0045] Step 1: In a nitrogen environment of 30 Pa, at 120° C., dimethyl zinc (DEZ) is introduced in a pulse form, and zirconium dioxide reacts with DEZ. The pulse time is 60 seconds. After the reaction is completed, high-purity nitrogen (mass purity of 99.99%) is introduced to purge the reaction environment. The purge time is 60 seconds.
[0046] Step 2: At the same temperature and pressure as step 1, ultrapure water (second precursor) is introduced in pulse form for reaction, the pulse time is 60 seconds, and then high-purity nitrogen is introduced to purge the reaction to clean the reaction environment, and the purge time is 60 seconds;
[0047] Step 3, determine the number of sub-cycles according to different zinc and aluminum, and repeat steps 1 and 2 23 times in sequence;
[0048] Step 4: at the same temperature and pressure as step 1, trimethylaluminum (TMA) is introduced in a pulse form for reaction, the pulse time is 60 seconds, and then high-purity nitrogen is introduced to purge the reaction to clean the reaction environment, and the purge time is 60 seconds;
[0049] Step 5: At the same temperature and pressure as step 1, ultrapure water (second precursor) is introduced in a pulse form for reaction, the pulse time is 60 seconds, and then high-purity nitrogen is introduced to purge the reaction to clean the reaction environment, and the purge time is 60 seconds;
[0050] Step six, according to the difference in zinc-aluminum ratio, after each plating of aluminum source and oxygen source, a parent cycle is completed. Different parent cycles can be determined according to different needs, that is, repeating steps one to five twice in sequence to obtain AZO modified zirconium dioxide antistatic thermal control pigment.
[0051] Preparation of zirconium dioxide-acrylate high reflective layer: weigh 10.0g acrylate, 50g anhydrous ethanol, 10g water, and 0.5g organosiloxane, stir evenly, add 40g zirconium dioxide powder, and then add 150g zirconium beads. After dispersing at 1200rpm for 2h, filter and apply it on a pre-treated substrate. After curing at 100℃ for 2h, the zirconium dioxide-acrylate high reflective layer can be prepared. The coating thickness is 100μm.
[0052] Preparation of AZO-modified zirconium dioxide-acrylate antistatic coating: 10.0g acrylate, 50g anhydrous ethanol, 0.5g organosiloxane, stir evenly, add 45g AZO-modified zirconium dioxide antistatic pigment, then add 150g zirconium beads, disperse at 1000rpm for 2h, filter and apply it on the above-mentioned zirconium dioxide-acrylate high reflective layer, and cure at 100℃ for 2h to prepare AZO-modified zirconium dioxide-acrylate antistatic coating, the coating thickness is 40μm.
[0053] Example 2
[0054] A low solar absorption antistatic thermal control coating of this embodiment is composed of a zirconium dioxide-organic silicon high reflective layer and an AZO-modified zirconium dioxide-acrylate surface layer. The specific preparation method involves the following process:
[0055] Preparation of ALD-modified zirconium dioxide-based antistatic thermal control pigment: AZO modification was performed on the surface of zirconium dioxide using ALD technology. The deposition parameters of ALD deposition of AZO are as follows: the zinc source is diethyl zinc, the oxygen source is water, and the aluminum source is trimethyl aluminum; the carrier gas is high-purity nitrogen; the deposition temperature is 125°C; the pressure in the cabin is 30Pa, the zinc source pulse time is 60s, the oxygen source pulse time is 60s, and the aluminum source pulse time is 60s; pulse and cleaning time: each zinc source and aluminum source pulse is followed by a 40s clean with high-purity nitrogen; the oxygen source pulse is 60s, followed by a 30s clean with high-purity nitrogen to wash away the reaction by-products and residual reactants, the zinc-aluminum ratio is 24:1, the sub-cycle period is 24, and the number of parent cycles is 2; the specific preparation process is carried out according to Example 1.
[0056] Preparation of zirconium dioxide-organic silicone resin high reflective layer: weigh 10.0g of silicone resin, 50g of acetone, and 0.5g of organosiloxane, stir evenly, add 40g of zirconium dioxide powder, and then add 150g of zirconium beads. After dispersing at 1200rpm for 2h, filter and apply it on a pre-treated substrate. After curing at 120℃ for 2h, the zirconium dioxide-organic silicone high reflective layer can be prepared. The coating thickness is 125μm.
[0057] Preparation of AZO-modified zirconium dioxide-organic silicone antistatic coating: 10.0g of silicone resin, 50g of acetone, and 0.5g of organosiloxane are stirred evenly, and then 45g of AZO-modified zirconium dioxide antistatic pigment is added, followed by 150g of zirconium beads. After dispersing at 1000rpm for 2h, the mixture is filtered and coated on the above-mentioned zirconium dioxide-organic silicone resin high reflective layer. After curing at 100℃ for 2h, the AZO-modified zirconium dioxide-acrylate antistatic coating can be prepared, and the coating thickness is 35μm.
[0058] Example 3
[0059] A low solar absorption antistatic thermal control coating of this embodiment is composed of a zirconium dioxide-potassium silicate high reflective layer and an AZO-modified zirconium dioxide-potassium silicate surface layer. The specific preparation method involves the following process:
[0060] Preparation of ALD-modified zirconium dioxide-based antistatic thermal control pigment: AZO modification was performed on the surface of zirconium dioxide using ALD technology. The deposition parameters of ALD deposition of AZO are as follows: the zinc source is diethyl zinc, the oxygen source is water, and the aluminum source is trimethyl aluminum; the carrier gas is high-purity nitrogen; the deposition temperature is 125°C; the pressure in the cabin is 30Pa, the zinc source pulse time is 60s, the oxygen source pulse time is 60s, and the aluminum source pulse time is 60s; pulse and cleaning time: each zinc source and aluminum source pulse is followed by a 40s cleaning with high-purity nitrogen; the oxygen source pulse is 60s, followed by a 30s cleaning with high-purity nitrogen to wash away the reaction by-products and residual reaction precursors, the zinc-aluminum ratio is 24:1, the sub-cycle period is 24, and the number of parent cycles is 2; the specific preparation process is carried out according to Example 1.
[0061] Preparation of zirconium dioxide-acrylate high reflective layer: Weigh 10.0g of inorganic potassium silicate resin, 50g of water, and 0.5g of organosiloxane, stir evenly, add 30g of zirconium dioxide powder, and then add 150g of zirconium beads. After dispersing at 1200rpm for 2h, filter and apply it on a pre-treated substrate. After curing at 80℃ for 12h and then at 120℃ for 2h, the zirconium dioxide-inorganic potassium silicate high reflective layer can be prepared. The coating thickness is 100μm.
[0062] Preparation of AZO modified zirconium dioxide-inorganic potassium silicate antistatic coating: 10.0g inorganic potassium silicate resin, 50g water, 0.5g organosiloxane, stir evenly, add 45g AZO modified zirconium dioxide antistatic pigment, then add 150g zirconium beads, disperse at 1000rpm for 2h, filter and apply it on the above zirconium dioxide-inorganic potassium silicate high reflective layer, cure at 80℃ for 12h, and then cure at 120℃ for 2h to prepare AZO modified zirconium dioxide-inorganic potassium silicate antistatic coating, the coating thickness is 30μm.
[0063] Comparative Example 1
[0064] This comparative example is the preparation of a single-layer AZO-modified zirconium dioxide-acrylate antistatic thermal control coating, and the specific preparation method is as follows:
[0065] Preparation of ALD-modified zirconium dioxide-based antistatic thermal control pigment: AZO modification was performed on the surface of zirconium dioxide using ALD technology. The deposition parameters of ALD deposition of AZO are as follows: the zinc source is diethyl zinc, the oxygen source is water, and the aluminum source is trimethyl aluminum; the carrier gas is high-purity nitrogen; the deposition temperature is 125°C; the pressure in the cabin is 30Pa, the zinc source pulse time is 60s, the oxygen source pulse time is 60s, and the aluminum source pulse time is 60s; pulse and cleaning time: each zinc source and aluminum source pulse is followed by a 40s clean with high-purity nitrogen; the oxygen source pulse is 60s, followed by a 30s clean with high-purity nitrogen to wash away the reaction by-products and residual reactants, the zinc-aluminum ratio is 24:1, the sub-cycle period is 24, and the number of parent cycles is 2; the specific preparation process is carried out according to Example 1.
[0066] Preparation of a single-layer AZO-modified zirconium dioxide-acrylate antistatic coating: 10.0g acrylate, 50g anhydrous ethanol, and 0.5g organosiloxane are stirred evenly, and then 45g AZO-modified zirconium dioxide antistatic pigment is added, followed by 150g zirconium beads. After dispersing at 1000rpm for 2h, the mixture is filtered and coated on a pre-treated aluminum alloy substrate. After curing at 100°C for 2h, the AZO-modified zirconium dioxide-acrylate antistatic coating is prepared, and the coating thickness is 145μm.
[0067] The performance tests were conducted on the above Examples 1-3, three double-layer AZO-modified zirconium dioxide-based antistatic thermal control coatings and the single-layer AZO-modified zirconium dioxide-based antistatic thermal control coating of Comparative Example 1. The test method is as follows:
[0068] Adhesion test
[0069] According to the test requirements of GJB2704A-2006 General Specification for Thermal Control Coatings of Spacecraft and GB / T9288-2021 Cross-cut Test for Paint and Varnish Film, the thermal control coatings in the embodiments and comparative examples were subjected to cross-cut tests. The results are shown in Tables 1 and Figure 2 shown.
[0070] Table 1 Adhesion test results of different embodiments and comparative examples
[0071] Test methods Example 1 Example 2 Example 3 Comparative Example 1 GJB2704A-2006 Available through Available through Available through Available through GJB2704A-2006 1 1 1 2
[0072] Optical performance testing of coatings
[0073] The solar absorption ratio of the coating was measured using a LAMBDA 950 UV-VIS-NIR spectrometer produced by Perkin Elmer, USA. The hemispherical emissivity of the sample in the 3-35 μm band at room temperature was measured using a TEMP 2000A emissivity meter developed by AZ Technology, USA. The results are shown in Table 2.
[0074] Table 2 Optical performance test results of different embodiments and comparative examples
[0075] Test methods Example 1 Example 2 Example 3 Comparative Example 1 Solar Absorption 0.119 0.110 0.115 0.165 Hemispherical emissivity 0.906 0.868 0.923 0.893
[0076] Coating resistivity test
[0077] Referring to the requirements of GB / T 31838.2-2019, the volume resistivity of the coating was tested. The results are shown in Table 3.
[0078] Test methods Example 1 Example 2 Example 3 Comparative Example 1 Volume resistivity / Ω·m <![CDATA[1.0×10 6 ]]> <![CDATA[2.8×10 6 ]]> <![CDATA[7.0×10 6 ]]> <![CDATA[5.1×10 5 ]]>
[0079] Electron irradiation test
[0080] The electron irradiation test is carried out in accordance with the requirements of GJB 2502.5-2006. This method is suitable for vacuum-electron irradiation simulation test of coating materials. The solar absorption rate (αs) of the coating material can be tested in situ at any time before, during and after the test. The test is safe and reliable. The results before and after electron irradiation are shown in Figure 3-Figure 4 and Table 4.
[0081] Table 4 Optical performance test results of Example 1 and Comparative Example 1 before and after electron irradiation
[0082] Before irradiation αs Before irradiation εh After irradiation, αs After irradiation εh Example 1 0.119 0.903 0.140 0.901 Comparative Example 1 0.165 0.893 0.185 0.895
[0083] After 300 thermal cycle tests at -196°C to 125°C, the coatings of Examples 1-3 showed no cracking, peeling, blistering, etc., and had stable optical properties and good adhesion, basically meeting the requirements of spacecraft for antistatic thermal control coatings.
[0084] The above describes the specific embodiments of the present invention. It should be noted that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essential content of the present invention.
Claims
1. A method for preparing a low solar absorptivity antistatic thermal control coating, characterized in that: The following steps are involved: Step 1, weighing a binder and a solvent, after the binder is completely dissolved, adding an additive and zirconium dioxide powder, dispersing at a speed of 1000rpm-2000rpm for 1h-3h, filtering and coating on a pre-treated substrate, and curing at 25℃-125℃ for 2h-24h to obtain a high reflective layer; Step 2, weighing a binder and a solvent, after the binder is completely dissolved, adding an auxiliary agent and an AZO-modified zirconium dioxide antistatic pigment, dispersing at a speed of 1000 rpm-2000 rpm for 1 h-3 h, filtering and coating on the high reflective layer prepared in step 1, curing at 25 ℃-125 ℃ for 2 h-24 h, and obtaining an antistatic coating on the surface of the high reflective layer; that is, the process is completed; Among them, AZO modified zirconium dioxide antistatic pigment is prepared according to the following steps: Place zirconium dioxide powder in the ALD reaction chamber and process it according to the following steps: Step 1: react with a zinc source in a nitrogen environment, and clean the reaction environment after the reaction is completed; Step 2: reacting with an oxygen source under the same conditions as step 1, and cleaning the reaction environment after the reaction is completed; Step 3: Repeat steps 1 and 2 in sequence; Step 4: react with an aluminum source under the same conditions as step 1, and clean the reaction environment after the reaction is completed; Step 5: Repeat step 2; Step 6: Repeat steps 1 and 5 at least once; then you are done; The deposition parameters are as follows: the zinc source is diethyl zinc or dimethyl zinc, the oxygen source is ultrapure water, and the aluminum source is trimethyl aluminum; the deposition temperature is 100 ℃-150 ℃; the chamber pressure is 20 Pa-100 Pa, the zinc source pulse time is 10 s-60 s, the oxygen source pulse time is 10 s-60 s, and the aluminum source pulse time is 10 s-60 s; the reaction environment is cleaned by the following operation: each zinc / aluminum source pulse is followed by a high-purity nitrogen purge for 20 s-60 s, the oxygen source pulse is 10 s-60 s, and then a high-purity nitrogen purge for 20-60 s to flush away the reaction by-products and residual reaction sources.
2. The method according to claim 1, characterized in that: Completing the operations of steps one and two once is a sub-cycle, and completing the operations of steps one to five once is a main cycle; the number of sub-cycles is set according to the zinc-aluminum ratio; different main cycles are determined according to anti-static requirements.
3. The method according to claim 1, characterized in that: The zinc-aluminum ratio is (8~50):1; the particle size of the zirconium dioxide powder is 50 nm-1 μm.
4. The method according to claim 1, characterized in that: In step 1, the mass ratio of the binder to the zirconium dioxide powder is (2-6):1, and the thickness of the high reflective layer is 100 μm-150 μm.
5. The method according to claim 1, characterized in that: In step 1, the particle size of the zirconium dioxide powder is 50 nm-1 μm.
6. The method according to claim 1, characterized in that: In step 2, the thickness of the electrostatic discharge coating is 30 μm-50 μm.
7. The method according to claim 1, characterized in that: In steps 1 and 2, the binder is silica sol, potassium silicate, lithium silicate, acrylate, isocyanate, silicone resin or epoxy resin; the solvent is anhydrous ethanol, acetone or water; and the auxiliary agent is organosiloxane.
8. An antistatic thermal control coating with low solar absorptivity prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method of AZO film layer coated zeolite molecular sieve molecular pollution adsorption material with antistatic performance, and adsorption device
CN110681349A